Uma investigação funcional do verbo modal deber no espanhol falado peninsular - Durigon, Vanessa Querino [UNESP] (2015)
This work aims at contributing with functionalist studies of modality by means of description and analysis of the modal verb deber (de) in spoken Peninsular Spanish language data, the intervenient factors in the interpretation of this modal being considered and explained. To found the analysis, which was performed through a synchronic perspective of language, the context of occurrence of the verb is considered in order to evaluate the effects of meanings associated with its employment, according to a proposal by Hengeveld (2004), who supports the characterization of modality within Functional Discourse Grammar (HENGEVELD; MACKENZIE, 2008). This choice is justified by the fact that the study of modality needs apparatus that deals with the linguistic structures that are inserted in real communicative situations of the language, and yet, it is necessary to acknowledge that modality is not a unique and coherent category. The context is conceived in this work as a group of parameters related to the subject (such as type of grammatical person, semantic features [human], [animate], and [control]), as well as to verb tense and mode, and to the presence of negation and other modalizing elements used before the modal verb. The development of this work tries to answer two key questions: (i) to which extent the values expressed by the modal deber relate to the semantic units of the Representational Level within Functional Discourse Grammar?; (ii) what linguistic elements characterize the objective and subjective deontic modalities, based on the proposal by Olbertz and Gasparini-Bastos (2013)? The data were extracted from authentic speech samples belonging to the project PRESEEA (Proyecto para el estudio sociolingüístico del español de España y de América).